Trajectory analysis of Mythimna Loreyi migration into Korea using the HYSPLIT model - Juhyeong Han; Sunghoon Baek; Xue-Jing Wang; Chun-Sen Ma; Kwang-Hyung Kim (Scientific Reports, 2025)
Abstract Migratory moth species have a negative impact on agriculture in Korea, causing economic crop losses for farming households. The moths fly a considerable distance from their origins and settle in Korea, where they live for several generational cycles, feeding and laying eggs until the arrival of cold winter hinders their overwintering. Therefore, it is important to determine the timing and location of the moths’ departure and arrival to prevent potential harm from invasive moths. The goal of this study is to select the most likely origin and destination of the migratory moths by using the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model when there is limited moth occurrence data at the potential origin and destination. The HYSPLIT model was adopted and modified to investigate the potential trajectory paths of the loreyi leafworm (Mythimna loreyi), using atmospheric data. Occurrence data of M. loreyi was collected from 18 trap sites in Korea and five in China, and fed into the HYSPLIT model to conduct backward and forward trajectory analyses. As a result, we successfully prioritized the most likely origins and destinations of M. loreyi in China and Korea, respectively, which has potential implications for subsequent validation of moth migration, using genotypic and phenotypic characterizations. In conclusion, our results show that it is feasible to use the HYSPLIT model simulation for the initial screening of the most likely origins of migratory moths, leading to more efficient and effective validation study of insect migration between countries.